Discovery of the male of Temnolopha matura Diakonoff (Lepidoptera: Tortricidae: Olethreutini) in South Thailand - Pinkaew, Nantasak (Zootaxa, 2011)
Temnolopha was proposed by Lower (1901) for two species; Fernald (1908) subsequently designated T. mosaica Lower as the type species of the genus. Diakonoff (1968) synonymized Temnolopha with Phaecadophora Walsingham but later (Diakonoff 1973) reinstated it as a valid genus. Members of the genus are medium-sized tortricid moths with long, porrect labial palpi with the median segment strongly sinuate and the apex conspicuously pointed (Lower 1901, Diakonoff 1973, Horak 2006). Wing venation is typical of Olethreutini, but the accessory cell is small with the chorda arising between R2 and R3 (Horak 2006). The male genitalia are characterized by a tegumen with a clavate or hooked and ventrally bristled uncus; large, flat, densely hairy, drooping socii; and at least slightly asymmetrical, broad valvae. The female has a single signum comprised of a patch of scobination with one or two larger central teeth and one or two flattened, elongate-to-quadrate sclerites (Diakonoff 1973, Horak 2006). The genus includes five species worldwide (Brown 2005): Temnolopha mosaica Lower from Australia, T. sponditis (Meyrick) from South Africa, T. matura Diakonoff from Borneo, T. biguttata Diakonoff from Borneo (Diakonoff 1973), and T. abstrusana Kuznetsov from Vietnam (Kuznetsov 1988).